2022
DOI: 10.1002/adma.202201679
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly and Repeatedly Reprogrammable Liquid Crystalline Elastomer via a Shape Memory Mechanism

Abstract: Realization of muscle‐like actuation for a liquid crystal elastomer (LCE) requires mesogen alignment, which is typically achieved/fixed chemically during the synthesis. Post‐synthesis regulation of the alignment in a convenient and repeatable manner is highly desirable yet challenging. Here, a dual‐phase LCE network is designed and synthesized with a crystalline melting transition above a liquid crystalline transition. The crystalline phase can serve as an “alignment frame” to fix any mechanical deformation vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…Of equal importance is that the PCL offers a crystalline transition widely explored for shape-memory functions. [30][31][32] The network was synthesized in four steps (Figure 1a): 1) norbornene-functionalized polycaprolactone (N-PCL) is prepared by ring-opening polymerization of ε-caprolactone; 2) a brush prepolymer is obtained via ring-opening metathesis polymerization of the N-PCL; 3) the terminal hydroxyl groups are partially converted to methacrylates via the reaction with 2-isocyanatoethyl methacrylate; 4) a crosslinked brush network is formed by radical polymerization of the methacrylate groups. In this design, four parameters, labeled as n, k, m, and f in Figure 1a, can be adjusted to tune the network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of equal importance is that the PCL offers a crystalline transition widely explored for shape-memory functions. [30][31][32] The network was synthesized in four steps (Figure 1a): 1) norbornene-functionalized polycaprolactone (N-PCL) is prepared by ring-opening polymerization of ε-caprolactone; 2) a brush prepolymer is obtained via ring-opening metathesis polymerization of the N-PCL; 3) the terminal hydroxyl groups are partially converted to methacrylates via the reaction with 2-isocyanatoethyl methacrylate; 4) a crosslinked brush network is formed by radical polymerization of the methacrylate groups. In this design, four parameters, labeled as n, k, m, and f in Figure 1a, can be adjusted to tune the network.…”
Section: Resultsmentioning
confidence: 99%
“…The PCL endows the network with crystallization capability. [30][31][32] The abundant urethane and ester bonds can both undergo covalent bond exchange at 140 °C catalyzed by dibutyltin dilaurate (DBTDL), giving rise to solid-state plasticity [28,29] (Figure 1b) that allows reconfiguring a planar sheet into a 3D structure such as the origami crane in Figure 1c. Specifically, an external load is applied when the material is at a sufficiently high temperature (140 °C) for dynamic bond exchange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shape memory polymer (SMP) is a smart material that can change its shape from a deformed state to a permanent shape. Recent achievements in this area include diversifying stimuli, 1–7 upgrading from one‐way SMP to two‐way SMP, 8–45 and implementation of multiple shape memory effect 1–7 . Compared with the colorful expectations at the beginning of the development of this type of material, however, their commercial application so far is very few.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, artificial soft actuators have excellent controllability over their shape, morphology, and color and demonstrate potential applications in artificial muscles, soft robotics, bioelectronics, information storage/decryption, and so on. Polymeric hydrogels are ideal candidate materials for fabricating actuators because of their compliant mechanical and biomimetic properties, diverse responsiveness, and flexible design. Upon external stimuli, responsive units and bond states and shapes of polymers principally change, which can produce motions or signals to actuators. For instance, strong and reversible metal–organic coordination is widely used for designing soft hydrogel actuators. , The bonding strength of such supramolecular association is adjusted by precisely controlling the binding constants of metal ions with ligands, which enables devices to tunable mechanical properties, toughness, and adhesion. Some actuators have fluorescence-color-switching behaviors under different pHs, light irradiations, or strains. Moreover, metal ions in hydrogel matrices promote their antibacterial and tissue-repairing capability. These pioneering works have demonstrated that metal-coordinate tough hydrogels (MCTHs) have significantly broadened the design and promising applications of hydrogel actuators in fields of, for example, material, engineering, and biological sciences.…”
mentioning
confidence: 99%